PENGARUH KOMPETENSI, PRAKTEK AKUNTABILITAS DAN MORALITAS INDIVIDU TERHADAP PENCEGAHAN (FRAUD) DALAM PENGELOLAAN DANA DESA - Ni Wayan Sariwati; Ni Komang Sumadi (UNHI Press, 2021)
Prevention of fraud in villages financial management is important on the implementation of villager governances. This researcher aims to determine the impact of competencing, practice of accountabilities and individual morality on prevention (fraud). The population used was all village officials in villages throughout the sub-district of Ubud, a total of 56 people. The technique of determining the sample is purposive sampling with multiple regression as a data analysis technique. From the test results, a competency variable does not have a significant impact on fraud prevention, accountability practices have a positive effect on fraud prevention. Meanwhile, individual morality has a negative impact on the prevention of fraud in the management of village funds in villages throughout the sub-district of Ubud.